Downstream effects of the pandemic? Spatiotemporal trends of quaternary ammonium compounds in suspended particulate matter of German rivers - Lennartz, Sophie; Koschorreck, Jan; Göckener, Bernd; Weinfurtner, Karlheinz; Frohböse-Körner, Andrea; Siemens, Jan; Balachandran, Sanjana; Glaeser, Stefanie P.; Mulder, Ines; Justus Liebig University Giessen (My University, 2024)
During the SARS-CoV-2 pandemic, the preventive use of antimicrobials such as quaternary ammonium compounds (QACs) surged worldwide. As cationic and surface-active biocides, QACs are only partly removed during wastewater treatment and may cause adverse ecological effects in the downstream environment. To understand the environmental consequences of increased disinfectant use during the pandemic, we investigated spatiotemporal QAC concentration trends in the suspended particulate matter (SPM) of three diverse German rivers. Covering pooled annual SPM samples from 2006–2021 and monthly samples from 2018–2021 collected by the German Environmental Specimen Bank, 31 QACs were quantified by high performance liquid chromatography–mass spectrometry. ∑QAC concentrations in annual samples differed by more than tenfold between rivers in the order Saar (average 6.7 µg/g) > Rhine (0.9 µg/g) > Mulde (0.3 µg/g). The strongest potential pandemic imprint was however observed in the Mulde (+67 %) and Rhine (+22 %). Besides pandemic dynamics, also seasonal variation and mineral content of SPM tentatively affected QAC concentrations. Exceedance of predicted no-effect concentrations for sediment suggest ecotoxicological risks for long-chained QACs already before the pandemic. Our study thus highlights the importance of monitoring the environmental effects of antimicrobial use during pandemics and calls for an urgent minimization of non-essential applications.
Keywords: ddc:630